2019
DOI: 10.18632/oncotarget.26817
|View full text |Cite|
|
Sign up to set email alerts
|

Lung cancer stem cells and their aggressive progeny, controlled by EGFR/MIG6 inverse expression, dictate a novel NSCLC treatment approach

Abstract: The lung cancer stem cell (LuCSC) model comprises an attractive framework to explore acquired drug resistance in non-small cell lung cancer (NSCLC) treatment. Here, we used NSCLC cell line model to translate cellular heterogeneity into tractable populations to understand the origin of lung cancers and drug resistance. The epithelial LuCSCs, presumably arising from alveolar bipotent stem/progenitor cells, were lineage naïve, noninvasive, and prone to creating aggressive progeny expressing AT2/AT1 markers. LuCSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…This staining pattern is in line with adenocarcinoma markers detected in tumor xenografts and indicate that both sublines are LAC cells. LAC is frequently associated with development of malignant PE, which occurs during disease progression [35]. The process of cancer progression is also accompanied by increased mutations in driver genes of LAC and likely contribute to CSC heterogeneity within tumor cells [24,35].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This staining pattern is in line with adenocarcinoma markers detected in tumor xenografts and indicate that both sublines are LAC cells. LAC is frequently associated with development of malignant PE, which occurs during disease progression [35]. The process of cancer progression is also accompanied by increased mutations in driver genes of LAC and likely contribute to CSC heterogeneity within tumor cells [24,35].…”
Section: Methodsmentioning
confidence: 99%
“…LAC is frequently associated with development of malignant PE, which occurs during disease progression [35]. The process of cancer progression is also accompanied by increased mutations in driver genes of LAC and likely contribute to CSC heterogeneity within tumor cells [24,35]. LAC cells in PE represent cell population released from tumor tissues via mechanism of epithelial-mesenchymal transition (EMT) characterized with down regulated cell-to-cell adhesion [34,43].…”
Section: Methodsmentioning
confidence: 99%
“…A large number of studies have confirmed that CSC also exists in lung cancer, and CSCs are considered to be the main cause of tumor recurrence and metastasis. 4 Yin-Yang 1 (YY1) is a member of GLI Kruppel family of zinc finger transcription factors and overexpressed in a variety of human cancer tissues, such as breast, colon, stomach, and prostate cancer. [5][6][7] Luo et al found that YY1 was highly expressed in esophageal cancer tissue, which was related to lymph node metastasis and clinical stage, and the prognosis of patients with YY1 high expression was poor, indicating that YY1 was closely related to the progress of esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer stem cells (CSCs) are a cell subset with properties of persistence or immortalization, self-renewal, and the potential to differentiate phenotypically in lung cancer or supporting tissues [4]. Lung CSCs may be involved in the occurrence and development of lung cancer and can provide novel therapeutic targets for treatment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer stem cells (CSCs) are a cell subset with properties of persistence or immortalization, self-renewal, and the potential to differentiate phenotypically in lung cancer or supporting tissues [4]. Lung CSCs may be involved in the occurrence and development of lung cancer and can provide novel therapeutic targets for treatment [4]. For example, Wu et al recently showed that depletion of the oncogene, prostate tumor overexpressed gene 1 (PTOV1), sensitized lung cancer cells to chemotherapy by reducing lung CSC-like traits [5].…”
Section: Introductionmentioning
confidence: 99%